IMPLEMENTATION OF SERVICE-LEARNING METHOD AS THE IMPACTFUL LEARNING STRATEGY IN BASIC EDUCATION - Tri Kristianti; Aulia Rahman Oktaviansyah; Febriana Anisa Putri (LP2M Universitas Ibrahimy, 2023)
As the implementation of meaningful learning on the basic education level, the Minister of Education, Culture, Research, and Technology (Kemdikbud Ristek) held a collaborative service-learning strategy entitled Kampus Mengajar. This program has been applied since the COVID-19 Pandemic spread out in 2019 and in 2022, it had five batches: Kampus Mengajar I, II, III, IV, and V. Each category has a different vision and mission to achieve the goal of students’ development in literacy, numeracy, and technology on the targeted schools. Kampus Mengajar III with the tagline “Belajar sambil berdampak” is expected to provide significant results, particularly for the schools’ partners. This community service program focuses on developing the student’s literacy, numeracy, and technology knowledge in SD Negeri 2 Karangnongko, Kabupaten Malang. Interviews, class observations, notes, and contextual strategies were applied to collect data during the program using service learning as the research method. In conclusion, this community service program provides significant advantages for students, such as increasing their learning motivation and achievement, however, corresponding improvements need to be explored in the future for better school development.